Public misperceptions about undocumented immigrants in United States. - Ortiz, Rosa Y. (Kansas State University, 2011)
Undocumented immigrants are an exploited and disenfranchised faction of society that garner counterfactual attitudes by the public. This study aims to dispel myths held among the public by contesting fiction with facts. First, I argue that media sources and misinformation have culpability in inciting the publics' misguided perceptions about undocumented immigrants. For example, the images propelled to viewers reproduce moral panics, stratification, subjugation, social injustice and the fallacious notion that Mexican‟s are representative of all Hispanic unauthorized immigrants. This thesis then examines the public opinion responses of participants from the CBS and New York Times monthly survey poll of May 2007, compared to academic and government sources on health care, terrorism, and economics. The analysis concludes that participants‟ responses reveal misconceptions on the usage of health care by undocumented immigrants; the threat of terrorism as a means to deny Hispanics citizenship; the economic impact of cost to benefit analysis of the undocumented; and that Mexicans are not representative of all undocumented immigrant groups.
Keywords: Immigration; Public opinion; Undocumented Immigrants; Perceptions; Media; Hispanics; Social Research (0344); Sociology (0626)